“I’m like kentang”: Bilingual Indonesians construction of identity in the era of transnationalism - Helnywati Helnywati*; Christine Manara (Indonesian JELT, 2019)
This study looks at bilingual Indonesians who experienced living abroad as sojourners. The study aims to explore their identity experiences and struggles as influenced by their interactions with other language(s) and culture(s). An open-ended questionnaire and interview questions were used to obtain information on the respondents’ short biodata and experiences abroad. Nineteen respondents participated in an online open-ended questionnaire, and a few respondents volunteered to be interviewed. The findings reveal that these bilinguals Indonesian sojourners find it challenging to explain themselves from the monocultural essentialists view of identity. They identify themselves strongly with both their home and host countries and cultures but remaining staying open to new possibilities of identities. Yet, there are also traces of contradicting and conflicting selves of belonging in both cultures.